2013
DOI: 10.1186/1471-2229-13-199
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of vernalization and response genes in bread wheat from the Yellow and Huai Valley of China

Abstract: BackgroundFlowering time greatly influences the adaptation of wheat cultivars to diverse environmental conditions and is mainly controlled by vernalization and photoperiod genes. In wheat cultivars from the Yellow and Huai Valleys, which represent 60%-70% of the total wheat production in China, the large-scale genotyping of wheat germplasms has not yet been performed in terms of vernalization and photoperiod response alleles, limiting the use of Chinese wheat germplasms to a certain extent.ResultsIn this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 34 publications
5
77
0
2
Order By: Relevance
“…between 293 and 300 cM on chromosome 5A (Table 2). In bread wheat, the three vernalization response genes (Vrn-1, Vrn-2, and Vrn-3) directly influence both flowering and maturity (Galiba et al, 1995;Dubcovsky et al, 1998;Iwaki et al, 2002), of which Vrn-A1 mapped to the long arm of chromosome 5A (Preston and Kellogg, 2008;Chen et al, 2013). In bread wheat, the three vernalization response genes (Vrn-1, Vrn-2, and Vrn-3) directly influence both flowering and maturity (Galiba et al, 1995;Dubcovsky et al, 1998;Iwaki et al, 2002), of which Vrn-A1 mapped to the long arm of chromosome 5A (Preston and Kellogg, 2008;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…between 293 and 300 cM on chromosome 5A (Table 2). In bread wheat, the three vernalization response genes (Vrn-1, Vrn-2, and Vrn-3) directly influence both flowering and maturity (Galiba et al, 1995;Dubcovsky et al, 1998;Iwaki et al, 2002), of which Vrn-A1 mapped to the long arm of chromosome 5A (Preston and Kellogg, 2008;Chen et al, 2013). In bread wheat, the three vernalization response genes (Vrn-1, Vrn-2, and Vrn-3) directly influence both flowering and maturity (Galiba et al, 1995;Dubcovsky et al, 1998;Iwaki et al, 2002), of which Vrn-A1 mapped to the long arm of chromosome 5A (Preston and Kellogg, 2008;Chen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Samples of DNA were genotyped at the University of Saskatchewan Wheat Genomics laboratory in Saskatoon, Canada, with the 90K Illumina iSelect SNP array that consisted of 81,587 SNPs (Wang et al, 2014). We also screened the two parents for polymorphism for photoperiod response (Ppd-B1 and Ppd-D1) (Beales et al, 2007), vernalization response (Vrn-A1 and Vrn-B1) (Chen et al, 2013), and height-reducing Rht-B1 (Ellis et al, 2002) genespecific markers at the Agricultural Genomics and Proteomics tillers, required 53 d to flowering and 90 d to maturity, was 70 cm tall, produced 3.1 Mg ha −1 grain yield, and had 13% grain protein content (Supplemental Material 1). Additional filtering was then done, as described in one of our previous studies by Perez-Lara et al (2016), to select only SNPs that segregated in a biallelic pattern based on data from multiple mapping populations available to our programs.…”
Section: Dna Extraction and Genotypingmentioning
confidence: 99%
“…В неко- торых исследованиях гаплотип экзона-4 выявляли в ходе анализа хроматограмм секвенирования соответствующих ампликонов (Zhang et al, 2015) или субклонов (Chen et al, 2013), а также с использованием KASP-генотипирования (Díaz et al, 2012). В отличие от предложенных в насто-ящем исследовании способов, они более трудоемкие, экономически затратные и требуют больше времени для получения результата, поскольку содержат большее число этапов анализа.…”
Section: Discussionunclassified
“…As Vrn-D1b has the same deletion in the first intron as Vrn-D1a at the Vrn-D1 locus, cultivars with the dominant Vrn-D1 allele identified in previous studies Euphytica Sun et al 2009;Zhang et al 2009;Jiang et al 2010;Zhang et al 2010;Zhao et al 2010;Chen et al 2013;Sun et al 2013) by a molecular marker designed to detect the deletion, included those with either Vrn-D1a or Vrn-D1b. They were specifically selected for this study to distinguish between the two genotypes.…”
Section: Plant Materialsmentioning
confidence: 99%
“…YHRR is the largest wheat zone, accounting for 60-70 % of the total wheat acreage in China (Jin 1996). Previous studies indicated that the dominant Vrn-D1 allele was the most widely distributed in Chinese wheat cultivars Sun et al 2009;Zhang et al 2009;Jiang et al 2010;Zhang et al 2010;Zhao et al 2010;Chen et al 2013;Sun et al 2013). However, the origin and distribution of the novel Vrn-D1b allele was not clear.…”
Section: Introductionmentioning
confidence: 96%